Vesicular transport systems in fungi. (November 2011) - Rodrigues, Marcio L; Nosanchuk, Joshua D; Schrank, Augusto; Vainstein, Marilene H; Casadevall, Arturo; Nimrichter, Leonardo
Canonical and unconventional mechanisms of secretion in many eukaryotic cells are relatively well known. In contrast to the situation in animal cells, mechanisms of secretion in fungi must include the capacity for trans-cell wall passage of macromolecules to the extracellular space. Although these mechanisms remain somewhat elusive, several studies in recent years have suggested that vesicular transport is required for trans-cell wall secretion of large molecules. Several fungal molecules, including proteins, lipids, polysaccharides and pigments, are released to the extracellular space in vesicles. In pathogenic fungi, a number of these vesicular components are associated with fungal virulence. Indeed, extracellular vesicles produced by fungi can interfere with the immunomodulatory activity of host cells. Fungal vesicles share many functional aspects with mammalian exosomes and extracellular vesicles produced by bacteria, plants and protozoa, but their cellular origin remains unknown. Here, we discuss the involvement of vesicular transport systems in fungal physiology and pathogenesis, making parallels with the mammalian, bacterial, protozoan and plant cell literature.